Formation of Self-Generated Gradients of Iodixanol - John Graham (The Scientific World Journal)
The formation of self-generated gradients of iodixanol from a solution of uniform concentration requires the use of vertical or near-vertical rotors. The density profile that is generated depends upon the sedimentation path length of the rotor, centrifugation time, RCF and temperature. Modulation of the starting concentration changes the density range of the gradient. This Protocol Article illustrates the effect of these parameters on gradient shape in a few selected rotors. Because the gradients are formed by the centrifugal field, they are highly reproducible and easy to execute.